(untitled) (Scientific journal of the Fergana State University, 2023)
The article reflects on the specifics of professional skills and practical experience required by a teacher in the process of working with creative students. Also, in the field of culture and art, proposals and recommendations were made on what the pedagogue should pay attention to in educating young people as professional and skilled artists, further improving their skills and talents. Particular emphasis is placed on the interest of creative students in the field not only through theory and practice, but also with pedagogical skills, the importance of bringing their creative abilities to the surface and development.